2015
DOI: 10.1090/s0025-5718-2015-02941-x
|View full text |Cite
|
Sign up to set email alerts
|

Odd perfect numbers, Diophantine equations, and upper bounds

Abstract: We obtain a new upper bound for odd multiperfect numbers. If N is an odd perfect number with k distinct prime divisors and P is its largest prime divisor, we find as a corollary that 10 12 P 2 N < 2 4 k . Using this new bound, and extensive computations, we derive the inequality k ≥ 10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Ochem and Rao [9] recently proved that N > 10 1500 . Nielsen [8] obtained the lower bound ω(N ) ≥ 10 for the number of distinct prime factors of N , improving on his last result ω(N ) ≥ 9 (see [7]).…”
Section: Introductionmentioning
confidence: 77%
“…Ochem and Rao [9] recently proved that N > 10 1500 . Nielsen [8] obtained the lower bound ω(N ) ≥ 10 for the number of distinct prime factors of N , improving on his last result ω(N ) ≥ 9 (see [7]).…”
Section: Introductionmentioning
confidence: 77%
“…The key ingredient in the proof of the upper bound for numbers with the Lehmer property is the following lemma given by Nielsen in his proof of the bound for odd perfect numbers. Lemma 2.1 (Nielsen, [7]). Let r, a, b ∈ N and x 1 , .…”
Section: A New Upper Boundmentioning
confidence: 99%
“…Pomerance showed in [8] that if n satisfies the Lehmer property, then n is squarefree and n < K 2 K , where K denotes the number of prime divisors of n. Moreover Renze in [9] gave a bound K ≥ 15. If additionally 3 | n, then K ≥ 40 · 10 6 and n > 10 36·10 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Nielsen [12] has proved that if N is an odd perfect number with k distinct prime factors and largest prime divisor P then…”
Section: The Set E P Has Density Zero In the Setmentioning
confidence: 99%
“…Note that Ochem and Rao's second inequality is stronger than the first as long as ω(N) ≤ 81. Nielsen [12] has shown that ω(n) ≥ 10. In a previous paper [23], the author improved on Ochem and Rao's result, showing that:…”
mentioning
confidence: 99%